Música e misoginia: os impactos de curto prazo nas atitudes frente à mulher e na agressão - Lima, Débora Cristina Nascimento de (2021)
The music industry, with increasingly sophisticated strategies, has been growing exponentially year after year. Consequently, it passes the most diverse types of messages in the lyrics of songs. Compost of symbolic elements, the music can help to break paradigms or help to maintain violence and inequality. However, we know little about the effects of misogynistic songs on attitudes toward women and aggression. Thus, the present study aimed to overcome this theoretical gap by research the effects of misogynistic songs on attitudes toward women and aggression. For this purpose, we conducted four studies. Study 1 was a literature review to get an overview of the studies with song lyrics. The results showed that the negative effects of songs are the most studied. Study 2 aimed to adapt and validate the Attitudes Toward Women Scale (AFM). Through exploratory (N = 224, M age = 32.46, SD = 10.87) and confirmatory (N = 254, M age = 30.2, SD = 10.99) factor analysis. The results pointed to a single-factor scale with satisfactory internal consistency. Study 3 (N = 261, M age = 29, 14, SD = 10.14) sought to investigate the relationships of attitudes toward women with ambivalent sexism, aggression, and personality. The results revealed negative and significant correlations between AFM and benevolent (r = -0.46), hostile (r = -0.52), and physical aggression (r = -0.10) sexism. Finally, the experiment conducted in Study 4 (N = 147, M age =29.4, SD=9.86) showed effects of misogynistic music on aggression, but not on attitudes toward women. These results partially confirm the hypotheses raised and are in line with another research. These results partially confirm the hypotheses raised and are in line with another research. Finally, we confirmed the theoretical assumption that exposure to violent media influences aggression, according to the General Model of Aggression.